Short- and long-term outcomes of robotic- versus laparoscopic-assisted early-onset gastric cancer: a propensity score-matched retrospective cohort study - Yihuan Qiao; Boyu Kang; Yichao Zhang; Jiawei Song; Shuai Liu; Qi Wang; Yajie Guo; Yunlong Li; Jun Zhu; Jipeng Li (BMC Cancer)
Abstract Background Early-onset gastric cancer (EOGC) is a distinct subtype of gastric cancer with increasing incidence, characterized by unique clinical and pathological features. This propensity score-matched retrospective cohort study aims to compare the perioperative safety and outcomes of EOGC patients who underwent laparoscopic versus robotic radical gastrectomy, providing a scientific basis for surgical treatment of EOGC. Materials and methods We included 252 patients diagnosed with EOGC at or before the age of 45, who underwent robotic or laparoscopic radical gastrectomy between January 2015 and April 2021. After propensity score matching, 47 patients in the robotic surgery group and 94 in the laparoscopic surgery group were compared. The study evaluated intraoperative and postoperative outcomes, pathological results, and long-term survival. Results The robotic surgery group showed less intraoperative bleeding (50 ml vs. 100 ml, p = 0.042) and shorter postoperative hospital stays (6 days vs. 7 days, p = 0.008) compared to the laparoscopic group. The number of positive lymph nodes was higher in the robotic group (median 2 vs. 1, p = 0.016), but the number of lymph nodes harvested did not significantly differ. No significant differences were found in overall survival (3-year OS: 65.9% vs. 62.5%, p = 0.596) and disease-free survival (3-year DFS: 61.4% vs. 61.7%, p = 0.765) between the two groups. Conclusions Robotic resection for EOGC is non-inferior to laparoscopic surgery in terms of perioperative outcomes and long-term prognosis. This study suggests that robotic surgery may be a viable option for the treatment of EOGC.